Induction of myelinating oligodendrocytes in human cortical spheroids - Madhavan, Mayur; Nevin, Zachary S.; Shick, H. Elizabeth; Garrison, Eric; Clarkson-Paredes, Cheryl; Karl, Molly; Clayton, Benjamin L. L.; Factor, Daniel C.; Allan, Kevin C.; Barbar, Lilianne; Jain, Tanya; Douvaras, Panagiotis; et al. (Nature methods, 2018)
Cerebral organoids provide an accessible system for investigations of cellular composition, interactions, and organization but have lacked oligodendrocytes, the myelinating glia of the central nervous system. Here we reproducibly generated oligodendrocytes and myelin in ‘oligocortical spheroids’ derived from human pluripotent stem cells. Molecular features consistent with those of maturing oligodendrocytes and early myelin appeared by week 20 in culture, with further maturation and myelin compaction evident by week 30. Promyelinating drugs enhanced the rate and extent of oligodendrocyte generation and myelination, and spheroids generated from human subjects with a genetic myelin disorder recapitulated human disease phenotypes. Oligocortical spheroids provide a versatile platform for studies of myelination of the developing central nervous system and offer new opportunities for disease modeling and therapeutic development. A method for generating cortical spheroids from human pluripotent stem cells produces maturing oligodendrocytes that can myelinate axons and model myelin disease and drug effects.